A Mesopotamian Background for the So-Called Aggadic 'Measures' of Biblical Hermeneutics? - Lieberman, Stephen J. (Hebrew Union College annual, 1987)
Five of the 'measures' (מדות) which the Midrash distinguishes in its interpretation of Scripture are expounded. Cuneiform analogues of each are cited, and the Rabbinic techniques known as noṭariqon (which takes a word as an abbreviation of a phrase) and gemaṭriah (interpretation by manipulating the numeric values of the letters of a written word) are treated at length. These two devices were known in cuneiform hermeneutics from eighth-seventh century B.C.E. Assyria, where numerological manipulation was called arû. Some constitutive uses of these devices in ancient Mesopotamia and in later Jewish writings are surveyed and analogues in other cultures are mentioned. This paper delineates the activities of Nabû-zuqup-kēna (ca. 760-680 B.C.E.), in whose library tablets using such hermeneutics are first attested, and the position of ummânu 'master' which his ancestors and descendants held in the Assyrian court is noted. The implications for biblical interpretation of the use of these methods in Mesopotamia at such an early date, before the completion of the Hebrew Bible, are broached. The question of the Near Eastern contribution to Hellenistic civilization is raised in the light of the cuneiform antecedents for these techniques whose Hebrew names are Greek and Latin in origin. It is noted that analysis distorts ancient hermeneutics.